Comparison of transforming growth factor beta expression in healthy and diseased human tendon. Issue 1 (December 2016) - Goodier, Henry; Carr, Andrew; Snelling, Sarah; Roche, Lucy; Wheway, Kim; Watkins, Bridget; Dakin, Stephanie
Abstract Background Diseased tendons are characterised by fibrotic scar tissue, which adversely affects tendon structure and function and increases the likelihood of re-injury. The mechanisms and expression profiles of fibrosis in diseased tendon is understudied compared to pulmonary and renal tissues, where transforming growth factor (TGF)β and its associated superfamily are known to be key drivers of fibrosis and modulate extracellular matrix homeostasis. We hypothesised that differential expression of TGFβ superfamily members would exist between samples of human rotator cuff tendons with established disease compared to healthy control tendons. Methods Healthy and diseased rotator cuff tendons were collected from patients presenting to an orthopaedic referral centre. Diseased tendinopathic (intact) and healthy rotator cuff tendons were collected via ultrasound-guided biopsy and torn tendons were collected during routine surgical debridement. Immunohistochemistry and quantitative real-time polymerase chain reaction were used to investigate the protein and gene expression profiles of TGFβ superfamily members in these healthy and diseased tendons. Results TGFβ superfamily members were dysregulated in diseased compared to healthy tendons. Specifically, TGFβ-1, TGFβ receptor (R)1 and TGFβ R2 proteins were reduced (p < 0.01) in diseased compared to healthy tendons. At the mRNA level, TGFβ R1 was significantly reduced in samples of diseased tendons, whereasTGFβ R2 was increased (p < 0.01).BMP-2, BMP-7 andCTGF mRNA remained unchanged with tendon disease. Conclusions We propose that downregulation of TGFβ pathways in established tendon disease may be a protective response to limit disease-associated fibrosis. The disruption of the TGFβ axis with disease suggests associated downstream pathways may be important for maintaining healthy tendon homeostasis. The findings from our study suggest that patients with established tendon disease would be unlikely to benefit from therapeutic TGFβ blockade, which has been investigated as a treatment strategy in several animal models. Future studies should investigate the expression profile of fibrotic mediators in earlier stages of tendon disease to improve understanding of the targetable mechanisms underpinning tendon fibrosis.